Risk Factors of Symptomatic COVID-19 in Samtse District, Bhutan - Karma Lhendup; Tsheten Tsheten; Tsheten Tsheten; Tshewang Rinzin; Kinley Wangdi (Frontiers Media S.A., 2022)
IntroductionAll Coronavirus disease 2019 (COVID-19) positive cases in Samtse District, Bhutan were isolated in the isolation facilities managed by the government hospitals. This study aimed to identify the socio-demographic risk factors for developing COVID-19 symptoms amongst these patients.Methods and MaterialsA secondary data of the COVID-19 positive cases from isolation facilities of Samtse District from 5 May to 7 September 2021 was used for this study. Survival analysis was carried out to estimate the cumulative probability of symptom onset time by each risk factor. Kaplan-Meier curves were used to estimate the probabilities for the onset of symptoms at different time points and a log-rank test was employed to assess the differences between covariates.ResultsA total of 449 patients were included, of which 55.2% were males and 73.3% (328) were aged >18 years. The mean age was 42 years with a range of 3 months to 83 years. Forty-seven percent (213) reported at least one symptom. Common symptoms were fever (32.3%, 145), headache (31.6%, 142), and cough (30.1%, 135), respectively. Males were 64% less likely to be symptomatic than females [adjusted hazard ratio (aHR) = 0.36, 95% confidence interval (CI) 0.183-0.917]. Farmers (aHR = 3.17, 95% CI 1.119-8.953), and drivers and loaders (aHR = 3.18, 95% CI 1.029-9.834) were 3 times more likely to be symptomatic compared to housewives. Residents of Samtse sub-districts were 5 times more likely to be symptomatic than those living in other sub-districts (aHR = 5.16, 95% CI 2.362-11.254).ConclusionThe risk of developing COVID-19 symptoms was being fe male, farmers, drivers and loaders, and residents of the Samtse sub-district. These high-risk groups should be provided additional care when in isolation facilities.